286 The impact of adverse childhood experiences on health: a systematic review and meta-analysis. (1st September 2016) - Hughes, Karen; Hardcastle, Katie; Bellis, Mark A
Abstract : Background: A growing number of studies are seeking to examine the long-term impacts of adverse childhood experiences (ACEs; including child maltreatment and exposure to family violence and other household dysfunction in childhood) on health and wellbeing. Synthesis of such studies is needed to provide policymakers and practitioners with evidence to support investment in effective prevention and support strategies. Methods: We undertook a systematic literature search to identify studies that measured the cumulative impact of ACEs on health harming behaviours (HHBs) and health outcomes in adulthood. Included studies measured at least four ACEs (covering both child maltreatment and dysfunctional family environments) and permitted the measurement of odds ratios for outcome measurements by ACE count up to 4+ ACEs. Data were extracted from included studies for outcomes relating to: violence; substance use; sexual behaviour; weight and exercise; mental health (including suicide); and chronic diseases. Meta-analyses were undertaken for outcomes covered by at least four studies. Results: Meta-analyses found a cumulative impact of ACEs on most outcomes measured, with risks (pooled odds ratios) increasing with ACE counts. Outcomes with the greatest impacts included self-directed violence; violence perpetration; violence victimisation; and problem alcohol and drug use. Conclusions: The cumulative relationship between ACEs and a wide variety of health and social outcomes is being identified in populations across the globe. Developing multi-agency understanding of the links between ACEs and adult outcomes is imperative to support the implementation of effective action to prevent child maltreatment, promote family wellbeing and support those affected by childhood adversity to ultimately prevent violence and improve population health.